The Influence of Education Level, Financial Literacy and Lifestyle on Investment Decision - Syauqina, Aisha Humayro; Munandar, Agus (Program Studi S1 Akuntansi Fakultas Ekonomi & Bisnis Univesitas Jenderal Soedirman, 2023)
This study aims to test shareholders' investment decisions from the perspective of education level, financial literacy and lifestyle. The methodology used is by utilizing purposive sampling techniques, a total of 90 individuals who have invested in the capital market will answer out a questionnaire as a primary data. The collected data is tested by multiple linear regression analysis, reliability, validity, heteroscedasticity, normality and multicolonierity, autocorrelation, determination, simultaneous and partial significant test. This study shows if lifestyle and education level will not affect investment decisions. Meanwhile, financial literacy variables partially affect investment decisions.